Pengaruh Labelisasi Halal Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Produk Indomie - WIDODO, Tri (2016)
With good economic growth, the number of people a lot, and the majority of the population is Muslim, Indonesia is a tempting market for the marketing of a product. So inundated by products and abroad. Therefore the Indonesian company must be besaing especially food products. Indonesian food companies are encouraged to be creative and innovative in implementing marketing strategies. To be able to dominate the market in their own country. One of these strategies is halal labeling and price of a product. And the purpose of this study was to determine whether the labeling of halal and prices affect the purchase decision Independent variables in this study are labeling Halal ( X1 ), Price ( X2 ). The dependent variable is the consumer's decision to buy instant noodle products. The sample used in this study were 100 respondents from the entire student population of the University of Muhammadiyah Surakarta. Methods of data collection in this study is primarily or directly from the questioner. Test the hypothesis in this study is t-test, f, and test ( R2 ) . The research result t test showed that halal label partially significant effect on purchases of products indomie indicated by a significant level of 0.001 <0.05. The research result t test showed the product price is partially significant effect on product purchasing decisions, demonstrated by a significant level of 0.004 <0.05. F test showed that the halal labeling and price menpunyai relationship and simultaneously (simultaneously) has significant influence on purchasing decisions instant noodle products. Effect of halal label and price with the decision to buy instant noodle products through test coefficient (Adjusted R2 ) with a value of 0318 or 31.8 %. Therefore, it can be concluded that the halal labeling and price are the most important factors affecting consumer purchase decisions.